Nanoparticle Translocation through Conical Nanopores: A Finite Element Study of Electrokinetic Transport. Issue 1 (26th September 2016) - Rempfer, Georg; Ehrhardt, Sascha; Holm, Christian; de Graaf, Joost
Abstract : Nanoparticle translocation through conical nanocapillaries using a simulation model based on the electrokinetic equations are theoretically investigated. The authors identify parameters for the maximum current modulation during translocation, investigate the dependence of the signal strength on the particle charge and size, and identify conditions preventing translocation or even trapping particles. Abstract : Recent years have seen a surge of interest in nanopores because such structures show a strong potential for characterizing macromolecules, e.g., DNA. Here, the authors theoretically investigate the translocation of a spherical nanoparticle through a conical nanocapillary, by numerically solving the coupled system of electrokinetic continuum equations. Based on their findings, the authors formulate simple guidelines for obtaining the maximum current signal during the translocation event, which should be transferable to other nanopore geometries. In addition, the dependence of the signal strength on particle properties, such as surface charge and size, is evaluated. Finally, the authors identify conditions under which the translocation is prevented by the formation of a strong electroosmotic barrier and show that the particle may even become trapped at the pore orifice, without imposing an external hydrostatic pressure difference.